Analisis Dampak Sektor Perkebunan terhadap Pertumbuhan Ekonomi Mengacu pada SDGs Indonesia 2021 - Safitri, Wahyuni; Gusniarti, Fadia; Al Ikhsan, M. David; Sherlyanti, Atika Putri; Nairobi, Nairobi; Nirmala, Tiara; Darmawan, Arif (Studi Ekonomi dan Kebijakan Publik, 2024)
Purpose: This study aims to explain the impact of the plantation sector on Indonesia's economic growth in 2021, focusing on Sustainable Development Goal (SDG) number 8, which emphasizes decent work and economic growth. Methodology/approach: This study adopts a quantitative approach using secondary data obtained directly from the Central Bureau of Statistics (BPS). Multiple Linear Regression is the method employed, along with testing for Classical Assumptions and T-statistics (partial test) using the STATA analysis tool. Results/findings: The research findings from the t-test indicate that out of the eight types of crops in the plantation sector, only tea significantly influences Indonesia's economic growth in 2021. Limitations: The limitations of this study include the number of dependent variables (eight) and the range of data time in 2021. Contribution: This research can serve as a reference for prioritizing the plantation sector, which has significant development potential, considering Indonesia's favorable geographical location. Therefore, it is expected that this potential can positively contribute to Indonesia's economic growth by aiming to achieve prosperity and Sustainable Development Goals (SDGs).